An analysis of the phenomenon Ime y’omwana movement in Kenyenya sub-county, Kisii County, Kenya - Nyangara, Makori A.; Naila, Napoo; Obwoge, Hezekiah (JOOUST)
The bewildering explosion of new religious movements in Africa forms a tremendous increase in number of splinter groups in Christianity. In this paper, we give an analysis of a phenomenon ImeY’omwana movement in Kenyenya Sub-County in Kisii County. ImeY’Omwana is separatist novel religious movement and it is a splinter group from Seventh Day Adventist church in Kenyenya Sub-county, Kisii County. The paper traces its origin from the reasons for the division from the main church, its beliefs and practices. It is curious to note that ImeY’omwana movement puts more emphasis on the son of God. They speak more on the son of God and they rarely speak of God.TheImeY’Omwana (IYM) inKisii language means literally in the Son of God. This a splinter group was started as protest against some tenets of the main church like tithing, righteousness by faith, baptism of the Holy Spirit, choice of leaders according to the level of education and offerings. The IYM began in Kenyenya Sub-County in Kisii County in 1979. Latter it moved to Gucha Sub-County then to Gucha South Sub-County, Masaba south sub-county all the way to Nyamira County. Experience of 31st December 1999 from Kenyenya sub-county showed that the IYM followers sold all their properties and made artificial wings in readiness to fly to heaven with Jesus upon the dawn of millennium. Those who tried to fly from the trees fell down broke their limbs and some even died. It is also alleged that the IYM followers do not take their children to school nor do they go to hospital for treatment.
1st JOOUST Scientific Conference